Mathematical Modeling of Turbulent Gas Flames and Assessment of Environmental Indicators of Modern Gas Burning Devices - K. V. Dobrego; S. A. Zhdanok; V. I. Timoshpolsky; I. M. Kozlov; V. A. Tishchenko; I. V. Kotov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper reveals the procedure of calculation of velocity fields, flame temperature and changes in concentration of the components of combustion products on the basis of time and length of a turbulent flame of gas-burning devices. This method is used to justify the selection of burners for state-of-the-art furnaces of the Republican Unitary Enterprise (RUE) «Byelorussian Steel Mills».